Multiple factors explain injury risk in adolescent elite athletes: applying a biopsychosocial perspective - von Rosen, P.; Frohm, A.; Kottorp, A.; Friden, C.; Heijne, A. (Scandinavian Journal of Medicine & Science in Sports, 2017)
Many risk factors for injury are presented in the literature, few of those are however consistent and the majority is associated with adult and not adolescent elite athletes. The aim was to identify risk factors for injury in adolescent elite athletes, by applying a biopsychosocial approach. A total of 496 adolescent elite athletes (age range 15-19), participating in 16 different sports, were monitored repeatedly over 52 weeks using a validated questionnaire about injuries, training exposure, sleep, stress, nutrition and competence-based self-esteem. Univariate and multiple cox regression analyses were used to calculate hazard ratios (HR) for risk factors for first reported injury. The main finding was that an increase in training volume, training intensity and at the same time decreasing the sleep volume resulted in a higher risk for injury compared to no change in these variables (HR 2.25, 95% CI, 1.46-3.45, p<0.01), which was the strongest risk factor identified. In addition, an increase by one score of competence-based self-esteem increased the hazard for injury with 1.02 (HR 95% CI, 1.00-1.04, p=0.01). Based on the multiple cox regression analysis, an athlete having the identified risk factors (Risk Index, competence-based self-esteem), with an average competence-based self-esteem score, had more than a threefold increased risk for injury (HR 3.35), compared to an athlete with a low competence-based self-esteem and no change in sleep or training volume.. Our findings confirm injury occurrence as a result of multiple risk factors interacting in complex ways.